2012
DOI: 10.3109/14767058.2011.605485
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for cesarean delivery: survey of maternal-fetal medicine physicians in the U.S.

Abstract: Objective To briefly describe practices concerning antibiotic prophylaxis for cesarean delivery among maternal-fetal medicine (MFM) physicians in the United States (US). Methods A 10-item self-administered survey about their routine use of antibiotics for cesarean delivery was mailed once only to a random sample of 1000 US-based fellows of the Society of Maternal-Fetal Medicine (SMFM) in November 2009. Results There were a total of 250 respondents from 40 US states between 10/09 and 4/2010, corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…A survey of maternal–fetal medicine physicians in the USA [14] found that only 2 (0.8%) of 245 respondents did not use routine antibiotics during CD. Approximately 95% of the physicians who used antibiotic prophylaxis stated that their drug of choice was either a first‐ or second‐generation cephalosporin; 85% administered antibiotics before incision, in line with the recommendations of the American College of Obstetricians and Gynecologists [15].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of maternal–fetal medicine physicians in the USA [14] found that only 2 (0.8%) of 245 respondents did not use routine antibiotics during CD. Approximately 95% of the physicians who used antibiotic prophylaxis stated that their drug of choice was either a first‐ or second‐generation cephalosporin; 85% administered antibiotics before incision, in line with the recommendations of the American College of Obstetricians and Gynecologists [15].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic antibiotics for caesarean section are commonly used worldwide, and in most institutions a single dose is administered, generally after clamping of the umbilical cord . However, a recent survey (published in 2011) of maternal and fetal medicine physicians in the USA revealed that 84% of those who responded (the response rate was 25%) used preoperative administration . The effectiveness of prophylactic antibiotics depends on their presence in effective concentrations throughout the operative period.…”
Section: Introductionmentioning
confidence: 99%
“…It has been advised that prophylactic antibiotics should be given before surgical incision to prevent post-operative surgical infections [6]; an exception in this generalization is the cesarean delivery, where the recommendation is to use prophylactic antibiotics after clamping of the umbilical cord. A recent survey that described practice of antibiotic prophylaxis for cesarean delivery among American maternal-fetal medicine physicians showed that; preoperative administration of antibiotic prophylaxis was the commonest practice which was reported by 84.6% of the physician compared to 15.0% who reported giving antibiotic prophylaxis after umbilical cord clamping [14]. …”
Section: Discussionmentioning
confidence: 99%